Biomechanical testing of an innovative fixation procedure to stabilize olecranon osteotomy. (November 2014) - Reising, Kilian; Konstantinidis, Lukas; Helwig, Peter; Wagner, Ferdinand C; Südkamp, Norbert P; Strohm, Peter C
For the treatment of distal humerus an approach involving olecranon osteotomy is frequently preferred as it offers a clearer view, especially in cases of complex intraarticular fractures. It is however associated with the high risk of osteotomy-related complications such as nonunion, delayed healing, implant failure and migration of wires. The aim of the present study was to evaluate the stability of different new procedures that stabilize olecranon osteotomy compared with conventional tension band wiring. We hypothesize that the new implants provide equivalent stability as the conventional tension band wiring. To test the hypothesis 27 biomechanically evaluated synthetic ulnae were osteotomized and stabilized with either the application of tension band wiring, the Olecranon Hook LCP (Synthes, Switzerland), or the Olecranon Osteotomy nail (Synthes, Switzerland). Loading was performed providing a tensile load to simulate the tensile force applied by the triceps muscle. Cyclic force-controlled loading was performed at 300 alternating forces between 10N and 500N at a speed of 200N/sec. An ultrasound-based system measured displacement to an accuracy of 0.1 mm. Statistical analysis showed significantly less displacement in the Olecranon Hook LCP and Olecranon Osteotomy nail groups compared with tension banding. Comparison of plate and nail yielded no differences in stability. Biomechanical testing did however show significantly higher stability for newer fixation methods for olecranon osteotomies compared with the frequently applied technique of tension band wiring. Whether the use of these implants will also lower complication rates remains to be evaluated in future clinical studies. Level of evidence : Basic Science Study, Biomechanical Study.